2020
DOI: 10.1177/1471301220977639
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of the COVID-19 pandemic on well-being and virtual care for people living with dementia and care partners living in the community

Abstract: The COVID-19 pandemic has necessitated public health measures that have impacted the provision of care for people living with dementia and their families. Additionally, the isolation that results from social distancing may be harming well-being for families as formal and informal supports become less accessible. For those living with dementia and experiencing agitation, social distancing may be even harder to maintain, or social distancing could potentially aggravate dementia-related neuropsychiatric symptoms.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 32 publications
2
72
0
1
Order By: Relevance
“…The pandemic produced psychological disorders, including depression, anxiety, and loneliness in elderly people with cognitive impairment living at home, suffering from a decrease in social activities [32]. Isolation and health needs have emerged as crucial issues for family experiences [33]. The disruption in routine activities has produced a significant overall decline and a reduced autonomy in daily living activities in care recipients, as reported by their caregivers [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic produced psychological disorders, including depression, anxiety, and loneliness in elderly people with cognitive impairment living at home, suffering from a decrease in social activities [32]. Isolation and health needs have emerged as crucial issues for family experiences [33]. The disruption in routine activities has produced a significant overall decline and a reduced autonomy in daily living activities in care recipients, as reported by their caregivers [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Carers of people with dementia faced particularly complex situations as studies report that many people with dementia find it difficult to follow public health restrictions. Carers also explained that reduced availability of support structures had an effect on behaviour that carers find challenging to respond to as well as on the cognition of people living with dementia (Carers UK 2020b;Eggert et al, 2020;Roach et al 2020;Vaitheswaran et al 2020).…”
Section: Availability Of Formal and Informal Supportmentioning
confidence: 99%
“…Evidence from several countries shows that large proportions of caregivers have experienced an increased burden and stress-related symptoms, like trouble sleeping, since the outbreak of the pandemic [e.g., (9,13,22,23)]. Furthermore, informal caregivers frequently reported worsened physical and mental health, such as being depressed or anxious as well as feeling more socially isolated and lonely [e.g., (9,24,25)]. Based on these considerations, we formulated the following hypotheses: H1: COVID-19 and its accompanying control measures lead to an increase in the frequency of providing informal family care to those who rely most strongly on personal care.…”
Section: Introductionmentioning
confidence: 99%
“…(28)], more and more studies have recently reported higher rates of depression and greater loneliness since the onset of the pandemic with respect to older adults (29)(30)(31), as well as higher levels of stress, anxiety, and depression among people with health problems or dementia (32)(33)(34). In this respect, other studies emphasized reduced opportunities for social interaction and made use of examples in which caregivers reported that their relatives with dementia were frustrated as it was difficult for them to understand why they should not go out or had to reduce contacts (25). This coincides with observations that caregivers in many countries reported a worsening of the care situation (9,32).…”
Section: Introductionmentioning
confidence: 99%